The effect of external factors moderated by digital literacy on the actual use of e-learning during the Covid-19 pandemic in Islamic universities in Indonesia - Sumin Sumin; Kahirol Mohd Salleh; Nurdin Nurdin (Sekolah Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2021)
The future of education is increasingly worrying due to the impact of the Covid-19 pandemic since the end of 2019. Restrictions on community activities and campus closures have forced university administrators to use e-learning. On the other hand, online learning has encountered many obstacles. Barriers to the use of e-learning are thought to stem from external problems (online facilities and infrastructure) or educators and students (internal factors), such as lack of literacy, low absorption, level of understanding, and other non-technical factors. This study aims to examine further the influence of external factors and digital literacy and the moderating effect of digital literacy with external factors (System Design, User Friendly, Devices, Internet, Electricity) on the actual use of campus e-learning at Islamic universities. This study found that: External factor variables have a significant positive effect on the actual use of e-learning. The digital literacy variable has a significant positive effect on the actual use of e-learning. The digital literacy variable weakens the influence of external factors on the actual use of e-learning at Islamic universities in Indonesia.